Demotivating factors of learning second foreign language: The case of Chinese language learners in Ghana - Nkrumah, Bright (Journal of Foreign Language Teaching and Learning, 2021)
Demotivation is a negative counterpart of motivation that affects student learning process and outcome. The present study attempted to determine the demotivating factors in learning a second language in Ghana using the Chinese language as a case study. A structured survey questionnaire data were collected from two hundred students learning Chinese at the University of Ghana to achieve the stated objective. The study identified the significant demotivation factors affecting students learning a second language: Teacher competence and teaching style, learning materials, crowded classroom, high competition in acquiring scholarship to China, less chance to get Chinese Ambassador Scholarship Award, and lack of self-confidence and experience of failure. Teachers should use more appropriate textbooks to improve their teaching skills. Also, students should be motivated to learn and participate in classroom activities to form lasting reminiscences.